Nitric oxide reduces oxidative stress generated by lactofen in soybean plants - Ferreira, Leonardo Cesar [UNESP]; Cataneo, Ana Catarina [UNESP]; Ramazzini Remaeh, Ligia Maria [UNESP]; Corniani, Natalia [UNESP]; Fumis, Terezinha de Fátima [UNESP]; de Souza, Yara Andreo; Scavroni, Joseane [UNESP]; Aparecido Soares, Bruno Jose [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
Nitric oxide (NO) is a molecule able to directly scavenge ROS and end chain reactions, which can be generated by some herbicides This study aimed to evaluate whether the pretreatment of soybean plants with sodium nitroprusside (SNP) solution, a NO-donor substance, provides protection against oxidative stress generated by lactofen Soybean plants were pretreated with SNP before lactofen application The levels of lipoperoxides and photosynthetic pigments were quantified, and the activity of the antioxidant enzymes glutathione S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) was assessed Although lipid peroxidation was not completely prevented. NO was able to scavenge ROS generated by the lactofen action, avoiding the photosynthetic pigment breakdown Consequently. ROS scavenging by NO leads to a decrease in the available substrate for the antioxidant enzymes SOD, CAT, and POD, which are essential to protect plants under oxidative stress situations such as absence of GST induction by H(2)O(2) (C) 2009 Elsevier Inc All rights reserved
Keywords: Antioxidant enzymes; Glycine max L Merril; Herbicides; Lipoperoxides; Photosynthetic pigments